Efficacy and Safety of Percutaneous Radiological Gastrostomy (PRG) as a Rescue Measure for Enteral Feeding in Patients with Advanced Head, Neck, and Upper Digestive Malignancies - Kumar, Mukesh; Chahal, Anurag; Malla, Sundeep; Bharti, Sachidanand G.; Kumar, Sunil; Biswas, Ahitagni; Sahoo, Ranjit; Pramanik, Raja; Pathy, Sushmita; Bhaskar, Suman; Chandrashekhara, S.H.; Sreenivas, V.; Thulkar, Sanjay (Indian Journal of Radiology and Imaging, 2022)
Background Percutaneous radiologic gastrostomy is an established mode of enteral feeding for nutritional support for patients with dysphagia from upper digestive tract malignancy. Its role as a rescue measure in patients with advanced malignancy, presenting with absolute dysphagia and failure of nasogastric tube insertion has not been well established.Purpose This study was performed to assess technical success and long-term outcomes of percutaneous radiologic gastrostomy (push type) for nutritional support for patients with absolute dysphagia as a last ditch nonsurgical rescue effort for enteral access.Materials and Methods This was a prospective observational study of 31 patients who underwent push-type percutaneous radiologic gastrostomy over a period of 2 years (March 2017–March 2019). The study was a part of a larger trial approved by the institutional ethics committee. Patients were followed till the removal of tube, death, or 1 year, whichever was earlier. Gastrostomy tube-related problems and complications were documented. Descriptive summary statistics were employed to analyze the success rate and complications.Results Thirty-one patients with mean age 56 years (26–78 years) including 18 males and 13 females with head and neck squamous cell cancer and esophageal cancer presenting with absolute dysphagia or significant dysphagia with failed nasogastric or endoscopic enteral access were included. Overall technical success was 93.5% (29/31), achieved in 26/31 patients with just fluoroscopy guidance and 3/5 patients with computed tomography guidance. One major (3.3%) and two minor (6.5%) complications were encountered. Five out of 29 gastrostomy tubes had to be exchanged, after a mean of 44 days (1–128 days) after insertion.Conclusion Percutaneous radiologic gastrostomy is a safe and effective intervention even as a rescue measure in patients with absolute dysphagia from advanced upper digestive tract malignancies.
Keywords: gastrostomy; head and neck cancer; esophageal cancer